The Behavioral Islamic Finance: Conceptual Framework and Literature Review - Risman, Asep (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
In this paper, we propose a conceptual framework of behavioral Islamic finance, we redefine intention as an action or condition that precedes behavior. This paper examines theories, expert opinions, and several research results from scientific papers and articles as well as books from several scientific disciplines other than financial management, then makes reasoning and sequence. This paper proposes redefining intentions as actions or states that precede behavior, other than intentions in the heart. Also, some definitions and propositions of relationships between constructs are expected to be helpful for future scholarship and studies on behavioral Islamic finance and other behavioral finance studies.